Hydrothermal Synthesis, Crystal Structure and Optical Properties of A 2-D Organic-Inorganic Compound Mn(V2W4O19)(bpy)(Hbpy)2 (bpy = 4,4’-Bipyridine) - WANG, CHONG-CHEN (Asian Journal of Chemistry, 2010)
A hydrothermal reaction of NH4VO3, WO3, MnCl2 and 4,4'-bipyridine yields a novel organic-inorganic hybrid compound, Mn(V2W4O19) (bpy)(Hbpy)2 (bpy = 4,4'-bipyridine) (C30H26N6MnO19V2W4, Mr = 1666.79), which was characterized by elemental analysis, IR, singlecrystal X-ray diffraction analysis and UV-Vis-NIR diffuse reflectance spectrum. It crystallizes in monoclinic, space group C2/c with a = 19.931(2) Å, b = 11.4920(12) Å, c = 16.0917(19) Å, β = 96.432(2)º, V = 3662.6(7) Å3, Z = 4, Dc = 3.023 Mg/m3, μ = 13.424 mm-1 and F(000) = 3068. The final R = 0.0630 and wR = 0.1679 for 3234 observed reflections with I>2σ(I). In the crystal, each Mn(II) is six-coordinated by two oxygen atoms from two [V2W4O19]4- and two nitrogen atoms from two bidentate bpy ligands and two nitrogen atoms from two protonated and terminal bpy ligands. The title compound is found to have an optical energy gap of 2.1 eV from UV-Vis-NIR diffuse reflectance spectrum.